The Effect of Web-Based Learning on The Speaking Skills of Class X Students In SMA Terbuka Kepanjen - Wardatun Nabila (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Information technology (IT) is something that is always hotly discussed by the community and is always followed by its development. Education is also one of the most significant aspects of life. Online-based education or better known as E-Learning is a concept in education that involves the use of technology to actively conduct distance learning. Speaking is one of the basic skills that every student must master to be able to interact carefully.Education is also one of life’s most significant aspects. This country will develop into a developed country with educated citizens who will improve the country. As a result, education is supposed to improve the globe. One of them is that we will fall far behind the others if we learn without learning. Online-based education, often know as E-Learning is a concept in education that involves using technology conduct distance learning actives (Ahmadi, 2014) so that education and learning are no longer limited to one space and time. Given that English is one of the required subject in Indonesia’s secondary school curriculum, the demand for English speaking abilities is growing in the contemporary global era, particularly among graduates of Indonesia’s vocational high scholl.in Indonesia, EFL learning technology research is critical (Bashori et al., 2020). According to (Rodrigues & Vethamani, 2015) use of online learning shows greater language proficiency and stronger self.This study aims to determine the effectiveness of using web-Learning for students' English learning at SMA Open Kepanjen. The researcher used an experimental research design. The researcher gave a pre-test, post-test, and delivery of a questionnaire. The researcher divided the class into two groups, one class as the control class and the other as the experimental class. Before learning, a Pre-Test was carried out in the two classes. Their control class received treatment with conventional learning methods and learning using Web Based Learning in the experimental class which was carried out for two weeks. Before doing post-testAll results were carried out to compare whether or not there was a difference between them. The results showed that there was no significant difference between the control class and the experimental class in using web-based learning. From the data that was tested using the Independent sample T-test, it showed a significance value of 0.622 > 0.05, so it was rejected. It also has the same result as the questionnaire which has a significance value of 0.615 > 0.05. This means that the use of e-learning at the SMA Terbuka Kepanjen is less effective but this learning method is very helpful for students to continue learning and as a new innovation in the world of education.Key Words: Open high school, Web-based learning, Speaking